Hubungan Kepercayaan Diri dengan Kejadiab Bullying Korban Bullying pada Remaja SMP - Viskhania Al Aulia Afita Ismi; Wahyu Endang Setyowati; Betie Febriana (STIKes Ibnu Sina Ajibarang, 2025)
Background: Adolescence, especially aged 12-19 years, is a transition period from children to adults who experience the development of all aspects or functions to enter adulthood. At this age, teenagers usually have an emotional attitude and many teenagers have not reached maturity and freedom, so many teenagers do things freely and are selfish in wanting to win for themselves, which gives rise to incidents of bullying. Bullying incidents continue to be a threat to Indonesian teenagers, both physical and non-physical bullying. The impact of bullying on victims will have health and mental disorders, sleep disorders, a feeling of wanting revenge and one of them is self-confidence. Method: This research is a type of quantitative research with a cross sectional approach. The sample used was students at Sultan Agung Islamic Middle School 4 Semarang. The technique used was random sampling of 112. The correlation test used in this research was gamma rank Results: Based on the results of the analysis, it was found that of the 112 research respondents, the majority had age characteristics of 13 years, 69 or 69 61.6% and female gender, 60 or 53.6%. The research results showed that 67.9% of teenagers had sufficient self-confidence, and 52.7% of teenagers who experienced bullying (victims of bullying) were. The results of the gamma rank test show a p value of 0.003 and the r value is found to be ( ) this indicates that there is a correlation in the same direction. Conclusion: There is a close relationshipbetween self-confidence and incidents of bullying (victims of bullying) in young women (p value 0.003)